FINANCIAMENTO PÚBLICO E GESTÃO FINANCEIRA EM SAÚDE: estudo de caso na Região Sul do Brasil - Gabriela da Silveira Oliveira (Universidade Federal do Maranhão, 2014)
The article presents an analysis on public health funding in the microregion of Osório between the years 2008- 2010 . This study aims to quantify the total amount of funds transferred to health by the federal and state and municipal levels, considering the percentage recommended by Constitutional Amendment No. 29/2000. Data collection was done through access to data from the National Public Budget in the Health System. The results showed the dependen ce of municipalities budget regarding the constitutional and legal transfers to complete actions and health services, despite significant application own resources in health, all municipalities exceeding the percentages provided by EC No 29/ 2000. It was evident, also, the minimal share of transfers from the state compared to significant transfers from the Union and own resources transferred and applied in health by municipalities. The per capita expenditure on health remained above the national average.